Hubungan Pengetahuan Ibu tentang Manajemen Laktasi dengan Keberhasilan ASI Ekslusif - Tiarnida Nababan; Viviani Nurhalisa; Sinta Sudari; Siska Nafisya; Vesta Christina Faustina (Universitas Malahayati Lampung, 2023)
ABSTRACT Exclusive breastfeeding is breast milk that is given to babies from birth for 6 months. Without adding or replacing with other foods and drinks except drugs, vitamins and minerals. Breast milk is a source of nutrition with a balanced composition and adapted to the needs of the baby's growth for 6 months. Breast milk contains dacossahexanoic (DHA) derived from omega 3 and arachidonic acid (AA) derived from omega 6 functions very important for children's brain growth. The problem of low exclusive breastfeeding is influenced by several factors, namely poor knowledge about breastfeeding, socio-culture related to behavior, giving solid food before the age of 6 months, health facility policies that do not support breastfeeding, promotion of formula milk, lack of support for skills inadequate in the community, workplace policies that do not support breastfeeding women and poor lactation management. The purpose of this study was to determine the relationship between maternal knowledge about lactation management and the success of exclusive breastfeeding in the Supiani Midwife Independent Practice in 2022. The design of this study used an analytical observational research method with a cross sectional approach aimed at determining. Exclusive Breastfeeding in Midwife Supiani's Independent Practice in 2022. The sample size in this study was all mothers who had babies aged 6-12 months in Supiani's Independent Practice Midwife in 2022. The total population was 30 people, so the sample size was 30 people. The type of sampling used in this study is the total sampling technique. The results obtained are seen from the p value, which is p = 0.013 0.05. The conclusion of this study states that there is a relationship between maternal knowledge about lactation management and exclusive breastfeeding in the Supiani Midwife's Independent Practice. Keywords: The Success of Exclusive Breastfeeding, Breastfeeding Mothers, Lactation Management. ABSTRAK ASI Ekslusif adalah Air Susu Ibu yang diberikan kepada bayi sejak dilahirkan selama 6 bulan. Tanpa menambahkan atau mengganti dengan makanan dan minuman lain kecuali obat, vitamin dan mineral. ASI merupakan sumber gizi dengan komposisi yang seimbang dan disesuaikan dengan kebutuhan pertumbuhan bayi selama 6 bulan. Masalah rendahnya pemberian ASI Ekslusif dipengaruhi oleh beberapa faktor yaitu pengetahuan yang buruk tentang menyusui, sosial budaya yang berkaitan dengan perilaku, dilakukan pemberian makanan padat sebelum usia 6 bulan, kebijakan fasilitas kesehatan yang tidak mendukung pemberian ASI, promosi susu formula, kurang adanya dukungan terhadap keterampilan yang memadai dimasyarakat, kebijakan tempat kerja yang tidak mendukung wanita menyusi dan manajemen laktasi yang buruk. Adapun tujuan dari penelitian ini untuk mengetahui pengetahuan ibu tentang manajemen laktasi dan bayi yang mendapatkan ASI Ekslusif. Desain penelitian ini menggunakan metode penelitian observasional analtik dengan penedekatan yang digunakan adalah cross sectional. Ibu yang mempunyai bayi usia 0-6 bulan menjadi sampel pada penelitian ini, maka populasi yang akan diambil sebanyak 30 responden. Jenis pengambilan sampel yang digunakan pada penelitian ini adalah dengan teknik total sampling. Hasil penelitian yang diperoleh dilihat dari nilai p yang yaitu p=0,0130,05. Kesimpulan penelitian ini menyatakan bahwa terdapat Hubungan Pengetahuan Ibu Tentang Manajemen Laktasi Dengan Pemberian ASI Ekslusif di Praktek Mandiri Bidan Supiani. Kata Kunci : Keberhasilan ASI Ekslusif, Ibu Menyusui, Manajemen Laktasi.